2014
DOI: 10.1017/s1047951114001474
|View full text |Cite
|
Sign up to set email alerts
|

Reducing patient radiation exposure during paediatric SVT ablations: use of CARTO® 3 in concert with “ALARA” principles profoundly lowers total dose

Abstract: Addition of CARTO® 3 to ALARA protocols markedly reduced radiation exposure to young people undergoing supraventricular tachycardia ablation while allowing for equivalent procedural efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…We would also advocate for the use of 3D systems to help reduce radiation exposure. There have been multiple studies showing a marked reduction in radiation exposure to the patient with 3D systems, and we would believe that the combination of radiation reduction, as demonstrated by others, and improvement in success rates, as demonstrated in our work, makes for a compelling argument for the utility of 3D mapping systems for pediatric WPW ablation …”
supporting
confidence: 62%
“…We would also advocate for the use of 3D systems to help reduce radiation exposure. There have been multiple studies showing a marked reduction in radiation exposure to the patient with 3D systems, and we would believe that the combination of radiation reduction, as demonstrated by others, and improvement in success rates, as demonstrated in our work, makes for a compelling argument for the utility of 3D mapping systems for pediatric WPW ablation …”
supporting
confidence: 62%
“…Recently, these systems have been employed for other ablation substrates including AV nodal re‐entry tachycardia, concealed accessory pathways (APs), and Wolff‐Parkinson‐White syndrome (WPW) because of the additional benefit of reducing or eliminating radiation exposure . There have been multiple studies highlighting the role of these systems to enable ablation of supraventricular tachycardia (SVT) substrates with decreased (or zero) radiation exposure to both patient and staff . Many of these studies have secondarily demonstrated that acute success rates with ablation using 3‐D mapping systems are comparable, with a focus on non‐inferiority.…”
Section: Introductionmentioning
confidence: 99%
“…With the accuracy offered by this modality, it should be a natural progression towards minimizing/completely eliminating fluoroscopy from most cardiac ablation procedures. However, although the use of fluoroless ablation of supraventricular arrhythmias is being aggressively pursued in the pediatric population, 5,[10][11][12][13] fluoroless ablation in the adult patient has been described in only a few studies from Europe, and with limited data from the United States. Kerst et al 14 presented an observational series of 30 patients, including 12 children, 29 of whom underwent successful fluoroless ablation for right and left atrial arrhythmias using a contact force-sensing catheter, and ICE imaging for CS cannulation.…”
Section: Discussionmentioning
confidence: 99%